DEMNITATEA UMANĂ, CONDIȚIE A EXISTENȚEI UMANE SAU CONSTRUCT SOCIAL (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Human Dignity, the Condition of Human Existence or Social ConstructOut of his constant striving to define the human dignity concept as a social construct shaped by political, material and segregational means, or as a valid existential condition in itself, The human being faces on the one hand, personal traumas and social tragedies, emerged from, and cultivated by social construct itself, or, on the other hand, experiences relational peace and respect based on his human condition as created man. The twentieth century would prove once more, if it were necessary, the frailty of human dignity as a social construct and would create the premises for comprehending human dignity as man’s existential condition. The philosophical ideologies marked by profound gaps in defining human dignity concept, couldn’t replace the human dignity biblical concept, which is able to guarantee both man’s inner integrity, his social and relational integrity, and the basis of God-man relationship.